Development of a knowledge translation taxonomy in the field of health prevention: a participative study between researchers, decision-makers and field professionals - Aurélie Affret; Ollivier Prigent; Marion Porcherie; Olivier Aromatario; Linda Cambon (Health Research Policy and Systems, 2020)
Abstract Objectives The current literature lacks a detailed and standardised description of public health knowledge translation (KT) activities designed to be applied at local levels of health systems. As part of an ongoing research project called the Transfert de connaissances en regions (TC-REG project), we aim to develop a local KT taxonomy in the field of health prevention by means of a participative study between researchers, decision-makers and field professionals. This KT taxonomy provides a comparative description of existing local health prevention KT strategies. Methods Two methods were used to design a participative process conducted in France to develop the taxonomy, combining professional meetings (two seminars) and qualitative interviews. The first step involved organising a seminar in Paris, attended by health prevention professionals from health agencies in four regions of France and regional non-profit organisations for health education and promotion. This led to the drafting of regional KT plans to be implemented in the four regions. In a second step, we conducted interviews to obtain a clear understanding of the KT activities implemented in the regions. Based on data from interviews, a KT taxonomy was drawn up and discussed during a second seminar. Results Our work resulted in a KT taxonomy composed of 35 standardised KT activities, grouped into 11 categories of KT activities, e.g. dissemination of evidence, support for use of evidence through processes and structures, KT advocacy, and so on. Conclusions The taxonomy appears to be a promising tool for developing and evaluating KT plans for health prevention in local contexts by providing some concrete examples of potential KT activities (advocacy) and a comparison of the same activities and their outcomes (evaluation).